Analysis of Sea Transport Passenger Services on Passenger Satisfaction at the Gapura Surya Nusantara Terminal Tanjung Perak Port Surabaya - Nanda, Mochammad; Akhmad, Ekka Pujo Ariesanto; Prawirosastro, Carlos Lazaro (Universitas Hang Tuah, 2025)
This research aims to analyze sea transportation passenger services on passenger satisfaction at the Gapura Surya Nusantara Terminal, Tanjung Perak Port, Surabaya. The time used by researchers to conduct research during 6 months Land Practices (PRADA) at the Gapura Nusantara Terminal which is under the auspices of PT. Pelindo. This research uses a qualitative approach with descriptive research type. The data sources used are secondary data and primary data, for data collection techniques in the form of interviews, observation and documentation. The results of this research show that the service at the Gapura Surya Nusantara Terminal is good, seen from the aspects of safety, security, reliability, comfort, such as stretchers, CCTV, security posts, disturbance information, ticket printing machines, waiting rooms, toilets and others. However, there are factors that cause the loss of consumer confidence in the services provided by the Gapura Surya Nusantara Terminal, namely the unavailability of a suggestion box or website to accommodate complaints and suggestions, the condition of the smoking area which is a little dirty due to cigarette butts being thrown away carelessly, apart from that, passengers prefer to smoke. in the front area of ​​the waiting room rather than in a designated smoking room and there is minimal availability of rubbish bins.